2020
DOI: 10.1039/d0py00437e
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of epoxide monomers promoted by tBuP4 phosphazene base: a comparative study of kinetic behavior

Abstract: This contribution fills the need for quantitative mechanistic and kinetic information for epoxide polymerizations catalyzed by tBuP4 phosphazene base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
11
1
Order By: Relevance
“…1) [16]. On the other hand, higher alkylene oxides, such as butylene oxide (M3) and octylene oxide (M4), can be polymerized using t-Bu-P 4 virtually without side reactions, producing the corresponding well-defined polyethers with narrow dispersity and predictable molecular weights [16,21,24]. A detailed study using M3 revealed the living nature of this polymerization system.…”
Section: Fundamental Aspects and Applicable Monomer Scope Of T-bu-p4-catalyzed Aropmentioning
confidence: 99%
See 3 more Smart Citations
“…1) [16]. On the other hand, higher alkylene oxides, such as butylene oxide (M3) and octylene oxide (M4), can be polymerized using t-Bu-P 4 virtually without side reactions, producing the corresponding well-defined polyethers with narrow dispersity and predictable molecular weights [16,21,24]. A detailed study using M3 revealed the living nature of this polymerization system.…”
Section: Fundamental Aspects and Applicable Monomer Scope Of T-bu-p4-catalyzed Aropmentioning
confidence: 99%
“…Applicable epoxide monomers for t-Bu-P 4 -catalyzed AROP include alkylene oxides (e.g., butylene oxide) [16,21], styrene oxide [22], glycidyl ethers (e.g., benzyl glycidyl ether) [16,21], and glycidyl amines (e.g., dibenzyl glycidyl amine) [23]. The scope and limitations of the present polymerization system are summarized in Fig.…”
Section: Fundamental Aspects and Applicable Monomer Scope Of T-bu-p4-catalyzed Aropmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic superbase based on phosphazene can also provide an alternative means of synthesizing polyethers. [ 27,41,42 ] Due to the significant size and charge separation of the countercation, they can effectively act as bases rather than nucleophiles, thereby preventing other side reactions. However, the relatively lower basicity of the phosphazene family compared to metal hydroxides makes them useful in only limited cases such as polymerization using epoxide as a monomer.…”
Section: Overviewmentioning
confidence: 99%